Influence of Provision of Physical Facilities on Participation in Early Childhood Development and Education in Public Primary Schools in Embu County, Kenya - Kamwitha Anastasia Muthanje; Ibrahim Khatete; Andrew Riechi (European Scientific Journal, ESJ, 2019)
Mainstreaming of Early Childhood Development and Education (ECDE) in primary schools has been a policy in the Kenyan educational system. The philosophy isto induct the learner at this level into primary school environment. However, this is not without challenges. The children at this level of ECDE have not developed enough to independently function. This has led to the need to examine how they are coping. It is with this background that the researcher examined the influence of the provision of physical facilities on participation in ECDE in public primary schools in Embu County, Kenya. A total of forty-two ECDE teachers took part in the study. The main tool for data collection was a questionnaire, observation schedule, and document analysis. Quantitative method was used to analyse data using Statistical Package for Social Sciences (SPSS). Findings from the study indicated that physical facilities influenced children’s participation in ECD classes. This paper focuses on proposing the need for relevant stakeholders in education to invest in physical facilities so as to increase participation in early childhood development and education